Construindo a sustentabilidade dos povos da maré através da co-inovação - Castro, Maviael Fonsêca de (2014)
The prospect "livelihoods" leads us to think of subsistence strategies of the families, which are variable depending on the context and the worldviews built in the historical trajectory of each traditional community. The livelihoods are summaries of world views, perspectives, work's gear and specialties, combined in a process of adaptation to the place and its resources, printing prospects of living well as social learning. In this thesis we tried to reflect on the proposal of convergence to the collective construction of knowledge and innovation with traditional peoples. Currently the challenges of research for development are mostly related to forms of interaction between scientific and popular knowledge. Case studies about cobuilding efforts show that the process is permeated by specific configurations of social relations in every society; where the representations that each makes the other are strong makers of the behavior of the main participants of the process and have limited the desired interactions possibilities. So we try, through participant observation, make a contextual analysis of coping strategies; the social construction of knowledge in the establishment of a local system of knowledge and innovation and evaluate the presence of scientific research in this; and finally, examine the possibility of a new approach to research, based on coinnovation in the concrete context of the peoples of tide in Formoso river , Pernambuco, Brazil. In the study found a particular social group involved, and inserted in a complex network of influences and interference, pressures and opportunities. We found that the extraction of mangrove resources plays an important role in household livelihood strategies and to people of the tide to live on despite the difficulties, due to the existence of a consolidated identity. The identity is therefore perpetuated based on a way of life with strategies in permanent reconfiguration based on the exploitation of additional opportunities to the central productive and economic strategy (artisanal fisheries). Whereas appropriate following the proposal of a socially constructed reality looked like build innovations that ensure adaptive strategies, describing the local system of knowledge and innovation in both communities verifying that, in this case, these are structured with a focus on knowledge of common sense, but could be said to society through greater integration with science. The initial challenge for innovation to become a tool for the sustainability of tide people would seek conciliatory strategies between expert and traditional systems, pointing to possible dialogue converged network. The study of a case of co-innovation with Tamandare fishermen, around the oyster farming, showed that in addition to challenges related to knowledge hierarchy, identitarias issues and future project influence the dynamics of collaboration between researchers and artisanal fishermen.